Kidney Transplantation from Donors with Severe Disseminated Intravascular Coagulation. (26th February 2013) - Sibulesky, Lena; Gohh, Reginald; Charpentier, Kevin; Morrissey, Paul
Abstract : Disseminated intravascular coagulation (DIC) is a syndrome characterized by massive formation of thrombin, which can lead to renal dysfunction or failure. Many transplant centers are reluctant to accept the kidneys from donors with DIC especially if renal dysfunction is present. We developed protocol of machine perfusion followed by tissue plasminogen activator (tPA) infusion in order to treat and evaluate DIC kidneys prior to transplantation. The kidneys were placed on machine preservation with tPA added to the perfusate prior to transplantation. Three kidneys were transplanted from two donors who sustained gunshot injuries to the brain. A biopsy at the time of organ recovery documented widespread fibrin thrombi in approximately 80% of the glomeruli. Serial biopsies showed interval improvement following machine perfusion and a normal appearing kidney three months after successful transplantation. The histological presence of DIC in a deceased organ donor, even if associated with renal dysfunction, is not a contraindication to renal transplantation. Machine perfusion and tPA infusions may contribute to the recovery and successful transplantation of such kidneys.